The Messiah/Speaker and His Mission: A Linguistic Analysis of Isaiah 61:1-11 - Elisha Kwabena Marfo (Fakultas Filsafat Universitas Advent Indonesia, 2022)
While the mission motif of Isa 61:1-11 seems to be passed over in silence, this study investigates the passage using linguistic analysis and discovers the theological significance of the motif of mission. The study indicated how YHWH relates to His mission, through the Speaker—identified as the Messiah, and His redemptive purpose for all humanity. Mission is centered on YHWH’s empowerment of the Speaker to deliver comforting messages and give hope to the discouraged, accelerate the freedom of prisoners, and console the grieving since their anguish and sadness is about to be converted into cheer. The focus is on Israel, though the nations will witness and glory in Israel’s salvation and righteousness. In effect, there will be a sprouting forth of YHWH’s righteousness and praises from the peoples of all the nations—an expression that has the worldwide salvific mission of the speaker in view.